Pengaruh Lingkungan Sosial Terhadap Kinerja Penyuluh Keluarga Berencana Kota Palembang dan Kota Prabumulih - Lausa Isaberna; Sriati Sriati; Dadang Hikmah Purnama (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
In carrying out its role as a family planning instructor, the duties and functions of family planning instructors are also influenced by the people around them who can support their performance and hinder their performance. Family planning extension workers often interact with the community as program targets, either directly or indirectly. This research is intended to see how much influence the social environment has on the performance of family planning instructors. The research method used is quantitative. The data was collected using a questionnaire that had been tested for its validity and reliability. The population in this study were the Palembang and Prabumulih family planning instructors with a sample of 30 people and were taken using a purposive sampling technique. The results of this study indicate that the social environment has a significant and positive influence on the performance of the extension workers by 75 percent. This means that the better the social environment, the better the performance of the family planning instructors.